2011
DOI: 10.2147/dddt.s13818
|View full text |Cite
|
Sign up to set email alerts
|

Illicit methylphenidate use among Iranian medical students: prevalence and knowledge

Abstract: Background:Methylphenidate, a medication prescribed for individuals suffering from attention-deficit/hyperactivity disorder, is increasingly being misused by students.Objective:The aims of this study were to evaluate the frequency of methylphenidate use among a group of Iranian medical students and to assess their knowledge of methylphenidate.Methods:Anonymous, self-administered questionnaires were completed by all medical students entering the university between 2000 and 2007.Results:Methylphenidate users’ me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 28 publications
0
21
2
1
Order By: Relevance
“…In our sample, they were only consumed by respectively 1.5% and 0.8% of the participants in our sample. This is much lower than what has been reported in Switzerland (5.8%) 16 (P <0.001), Iran (4.9%-8.7%), 17,18 Australia (7.7%), 14 or United States (11.3%-18%).…”
Section: Discussioncontrasting
confidence: 58%
“…In our sample, they were only consumed by respectively 1.5% and 0.8% of the participants in our sample. This is much lower than what has been reported in Switzerland (5.8%) 16 (P <0.001), Iran (4.9%-8.7%), 17,18 Australia (7.7%), 14 or United States (11.3%-18%).…”
Section: Discussioncontrasting
confidence: 58%
“…In Lengvenyte et al study findings, students used drugs in order to study and they preferred short-term effects more than long-term effects (4). In all studies, improvement in concentration and increasing study hours were among the most important reasons (11,14,(20)(21)(22)(23)(24). According to Micoulaud-Franchi et al study, they were used for improving academic function in the first priority; in the second priority, for increasing lucubration; and in third place, for improving the attention and concentration (19).…”
Section: Discussionmentioning
confidence: 94%
“…Students that use CEs would experience major side effects, such as illusion, anxiety, irritability, tachycardia, and dangerous side effects such as addiction, seizure, and cardiovascular events (7,9). Some effects of methylphenidates are similar to cocaine's effect on the brain (9,13,14). According to studies in Iran, 41.7% of the Ritalin users use it to increase concentration (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have, however, found that healthy high school and university students use methylphenidate to improve concentration, alertness and academic performance, or for recreational purposes. 2,3,4,5 The term 'non-medical use' of prescription drugs is defined by the United Nations Office on Drugs and Crime as the taking of prescription drugs, whether obtained by prescription or otherwise, other than in the manner or for the reasons or time period prescribed, or by a person for whom the drug was not prescribed. 6 In contrast, offlabel use in the United States (US) implies that the regulations of the Food and Drug Administration (FDA) permit physicians to prescribe approved medications for other than their intended indications, and misuse refers to the wrong, improper use or misapplication.…”
Section: Introductionmentioning
confidence: 99%